2019
DOI: 10.1177/1526924819854481
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Share 35 Policy on Liver Transplantation Outcomes for Patients With Nonalcoholic Steatohepatitis

Abstract: Background: To examine the temporal variation and outcomes of liver transplantation between pre- and post-Share 35 eras for patients with nonalcoholic steatohepatitis. Methods: A retrospective analysis was performed among 4380 patients with end-stage liver disease from the United Network for Organ Sharing database from 2009 to 2017 due to primary diagnosis of nonalcoholic steatohepatitis or cryptogenic cirrhosis with body mass index greater than 30. Cox regressions were used to model the effect of Share 35 pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…These outcomes are also similar to those for the overall outcomes of liver transplantation in ANZ 4 . Some studies comparing post‐transplant patient and graft survival of patients with MELD ≥35 before and after introduction of Share 35 in the USA have also demonstrated similar outcomes, 8,13,19,20 whilst others have shown improved survival in the Share 35 era 11,21 …”
Section: Discussionmentioning
confidence: 97%
“…These outcomes are also similar to those for the overall outcomes of liver transplantation in ANZ 4 . Some studies comparing post‐transplant patient and graft survival of patients with MELD ≥35 before and after introduction of Share 35 in the USA have also demonstrated similar outcomes, 8,13,19,20 whilst others have shown improved survival in the Share 35 era 11,21 …”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, many of these predictors overlap with a tool developed by Karnam and colleagues, which used demographic data from SRTR to identify seven factors impacting 5-year survival in patients undergoing LT for NASH. 36 The factors included in the calculator that overlapped with our findings were: age at LT, functional status, hepatic encephalopathy, ventilatory support at LT, dialysis prior to LT. 14 , 16 , 17 , 15 , 18 , 19 , 20 , 26 , 28 The remaining two predictive variables in their study, serum creatinine and presence of transjugular intrahepatic portosystemic shunts, were not analyzed in our eligible studies. Our study also identified novel variables, likely because our review was not restricted to the SRTR database ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%